HAZARD REGRESSION WITH PENALIZED SPLINE： THE SMOOTHING PARAMETER CHOICE AND ASYMPTOTICS - 童行伟 胡涛 崔恒建 (Acta mathematica scientia, 2010)
In this article, we use penalized spline to estimate the hazard function from a set of censored failure time data. A new approach to estimate the amount of smoothing is provided. Under regularity conditions we establish the consistency and the asymptotic normality of the penalized likelihood estimators. Numerical studies and an example are conducted to evaluate the performances of the new procedure.